The Taxonomy for Learning, Teaching and Assessing: Current Practices at Polytechnics in Bangladesh and its Effects in Developing Students' Competences - Haolader, Faruque A.; Ali, Md Ramjan; Foysol, Khan Md (International Journal for Research in Vocational Education and Training, 2015)
Polytechnics in Bangladesh endeavour to produce quality graduates for national and international job markets. The quality of graduates depends on several factors. This study examines the implementation process of the polytechnic curriculum with the objectives of determining the current level of practices in learn-ing/teaching material design, in delivering curriculum content, in assessing students and its effect on students' competence development. Data was collected through observation, opinion survey and competence test. Qualitative and quantitative methodologies were used for data interpretation and analysis in this descriptive type of research study. Findings revealed that the learning materials are mainly theory oriented and mostly cover those contents usually common in exams. About half of teachers are aware of the taxonomy for learning, teaching and assessing, but they rarely put importance on it. In the classroom, teachers spend only a little time for delivering content at the level of apply/analyse. However, a significant number of tasks performed in labs are practical and occupation relevant and can be classified at higher levels of the taxonomy. In student assessment, the test-items assess mainly theoretical knowledge at the level of remember. The effect of these practices is reflected in demonstrating student performance in a competence test. The study concludes with some recommendations.